Underwater noise analysis - impact to communication link - Bahrami, Nima (2013)
This thesis presents and implements the “Underwater noise analysis-impact to communication data link”. The communication data link has to be asses in terms of data rate, noise immunity, operational communication range and power consumption. In this thesis has been focused on the impact of underwater noise to the performance of a data link. Simulation and modeling of the transmitter and receiver including modeling of several noises in channel with emphasis on the underwater noise level.